Pharmacological Therapy of Vascular Malformations of the Gastrointestinal Tract - Andrew Szilagyi; Maged P Ghali (Canadian Journal of Gastroenterology)
Vascular malformation (AVM) in the gastrointestinal tract is an uncommon, but not rare, cause of bleeding and iron deficiency anemia, especially in an aging population. While endoscopic coagulative therapy is the method of choice for controlling bleeding, a substantial number of cases require additional therapy. Adjunctive or even primary phamacotherapy may be indicated in recurrent bleeding. However, there is little evidence-based proof of efficacy for any agent. The bulk of support is derived from anecdotal reports or case series. The present review compares the outcome of AVM after no intervention, coagulative therapy or focus on pharmacological agents. Most of the literature encompasses two common AVMs, angiodysplasia and hereditary hemorrhagic telangiectasia. Similarly, the bulk of information evaluates two therapies, hormones (estrogen and progesterone) and the somatostatin analogue octreotide. Of these, the former is the only therapy evaluated in randomized trials, and the results are conflicting without clear guidelines. The latter therapy has been reported only as case reports and case series without prospective trials. In addition, other anecdotally used medications are discussed.